Efforts to Prevent Children from Becoming Victims of Sexual Violence Crimes Through an Integrated Justice System - Jannah, Miftahul; Wulandari, Andi Sri Rezky (Universitas Pahlawan Tuanku Tambusai, 2024)
Children victims of sexual violence must be protected, not allowed to be victims again. The aim of this study is to analyze efforts to prevent children from becoming victims of sexual violence through an integrated criminal justice system. The research uses normative-empirical law research, legislative-legislative approaches and conceptual. As a result of the research, a criminal law policy through the revision of the UNCITRAL is needed to prevent child victims of sexual violence from becoming victims again in the child's criminal justice system. The Child Criminal Justice System Act No. 11 of 2012 stipulates that the taking of witness testimony by electronic recording in Section 3 and Section 58 letter (a) can only be done outside a court or distance hearing and used as a basis for investigation. The victim's child only has to testify once at the stage of the investigation and is recorded electronically and used until the trial. The making of oaths and BAPs is used as a valid means of proof in the proof process based on the recording at the stage of the investigation carried out electronically.